Congo Red Dye Adsorption using Magnesium Hydroxide from Seawater Bittern - Jumaeri Jumaeri; Akhsanun Nadiyya; Agung Tri Prasetya; Woro Sumarni (Jurnal Kimia Sains dan Aplikasi, 2022)
The study of Mg(OH)2 from seawater bittern as an adsorbent for Congo red (CR) from an aqueous solution has been performed. This study aimed to determine the effect of pH, contact time, and initial CR concentration on CR adsorption by Mg(OH)2. The adsorption kinetics and isotherms of CR on Mg(OH)2 in an aqueous solution were also studied. The optimum adsorption was obtained at pH 8 within 90 minutes of contact time with an adsorption capacity of 46.3 mg/g for an initial CR concentration of 29 mg/L. The adsorption process followed the Freundlich isotherm model with an n value of 2.579 and the pseudo-second-order kinetic model with a k2 value of 0.0021 g mg−1min−1.